The evaluation of MRSA surveillance cultures by the number and combinations of anatomical sites - Grmek Kosnik Irena; Storman Alenka; Petrovic Ziva; Robnik Slavica; Dermota Urska; Zohar Cretnik Tjasa (Sciendo, 2017)
The identification of patients infected and/or colonised by methicillin resistant Staphylococcus aureus (MRSA) is necessary for the timely introduction of measures for infection control. We compared the diagnostic efficacy of combinations of MRSA surveillance swabs routinely taken by health institutions in the country.